Genetske okvare zdravstvenega osebja, izpostavljenega anestezijskim plinom - Ratkajec, Tihomir (Zdravniški vestnik, 2003)
Background. Whether the anaesthetic gases are hazardous to the operating room personnel is controversial The aim of this study was to estimate their geneticdamage using the method of sister chromatid exchanges in personnel working at one Slovenian hospital Methods. Two subgroups of operating room personnel, non-smokers, female were included in the study.` subgroup A (seven subjects) who were co-operating daily with inhalations anaesthetic gases during operations and subgroup B (six control subjects) who were seldom co-operating with the same gases. Monthly and yearly doses of received ionising radiation (IR) were measured on five subjects in the control subgroup, by thermo-luminous dosimeter one month before medical examination. Interview was used to obtain information aboutpersonal and family disease and working environment. Neurophysiological symptoms were revealed with Finnish Institute of Occupational Medicine. The exchanges of DNA material of a chromosome was evaluated by counting the number of sister chromatid exchanges in 50 methaphases per probe. Results. The subgroups were of equal age. Subgroup A subjects had 18years of working experience while thosefrom subgroupB had 20 years. Subgroup A subjects participated at six anaesthetic procedures per day (on average) and those from subgroup B at five. Five subjects of control subgroup B, who works in operating room for orthopaedic and injures room, received yearly dose of 0.14 mSv on average and cumulative dose of 3.8 mSv (permited effected equivalent dose is 50 mSv per year). Their mediane value of sisler chromatid exchanges was 6.7/cell while on the five subjects of subgroup A that were not exposed to IS, was 7.2/cell. (Abstract truncated at 2000 characters).
Keywords: Anestetiki inhalacijski; anestezijski plini; Anesthetics, Inhalation; genetske okvare; medicinske sestre; Occupational Exposure; Operacijska soba, nega; Operating Room Nursing; Poklicna izpostavljenost; Psihološki testi; Psychological Tests; Sestrska kromatida, izmenjava; Sister Chromatid Exchange